Project-Based Learning (PjBL) berbasis Sejarah Lokal: Model Efektif untuk Meningkatkan Kemampuan Berpikir Kritis dan Kreatif Siswa dalam Pembelajaran Sejarah - Rahmawati, B. Fitri; Suhupawati, Suhupawati; Zidni, Zidni; Saputra, Bambang Eka (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
Critical and creative thinking skills are competencies needed in the 21st century. Therefore, a learning model is needed that can improve both competencies, namely the local history-based project-based learning (PjBL) model. The purpose of this study was to determine the effectiveness of the local history-based Project-based Learning (PjBL) model in improving students' critical and creative thinking skills in history learning. This study used a quasi-experimental method with a pretest-posttest control group design. The study was conducted in class X with a sample of 170 people. Data collection used observation using an assessment rubric for students' critical and creative thinking skills, while data analysis used Manova with the help of SPSS 25.0. The results showed that the critical thinking skills of the group that learned using the local history-based PjBL model were better than the group that learned using the conventional model (mean PjBL group = 71; mean conventional group = 60). Likewise, the creative thinking skills of students in the local history-based PjBL group were better than students who learned using the conventional model (mean PjBL group = 81; mean conventional group = 59). This result is reinforced by the results of the Manova test where the F value for Pillai's Trace, Wilks' Lambda, Hotelling's Trace, and Roy's Largest Root is 2466.745 with significance (Sig.) = 0.000 <0.05. Likewise with the Tests of Between-Subjects Effects for critical thinking (F = 1222.236; p <0.001) and creative thinking (F = 4483.554; p <0.001) which means that the integrated PjBL model of Local History is effective in improving students' critical thinking and creative thinking skills both simultaneously and partially.